Screening of local and exotic germplasms of chilli (Capsicum annum) for drought tolerance - Khan, Kinza; Zahid, Najma Yousaf; Qureshi, Abdul Ahad; Mehmood, Khalid (Journal of Pure and Applied Agriculture, 2023)
Drought is one of the major threats of the arid region of Pakistan. Drought stress affects the yield of chilli with up to 50% reduction. In view of this problem, a study was conducted to explore the drought resistance of a local variety Tatapuri (V1) and an exotic variety Bonanza (V2). Pot experiment was conducted with three treatments T0 control (well-watered), T1 (75 % stress), T2 (50 % stress) and T3 (25 % stress) at vegetative and reproductive stages by three replications.